Biotechnology in the pulp and paper industry : 8th ICBPPI - International Conference on Biotechnology in the Pulp and Paper Industry 2001 : Helsinki, Finland); Viikari, Liisa, 1949-; Lantto, R. (Raija); ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 2002)
This book covers both basic and applied sciences in a rather specified area of pulp and paper manufacture. The basic science of lignocellulose enzymology and plant genetics is covered also in many other contexts, whereas the application of biotechnology in process and product development is thoroughly reviewed. All the latest advances as well as new ideas of the research field are covered. This book will serve as an updated and compact information package of biotechnical aspects and the most recent advances of the pulp and paper industry sector.
Trends in pulp and paper biotechnology -- Biotechnology in the pulp and paper industry. A challenge for change -- Chapter 3. Alterations of lignin biosynthesis have tissue-specific impact on cell wall formation -- Cellulases: Agents for fiber modification or bioconversion? The effect of substrate accessibility on cellulose enzymatic hydrolyzability -- Lignocellulose oxidation by low molecular weight metal-binding compounds isolated from wood degrading fungi: A comparison of brown rot and white rot systems and the potential application of chelator-mediated Fenton reactions -- Dislocations and balloon swelling in spruce kraft pulp fibres -- Effect of cellulases, xylanase and laccase/HBT -- Recent developments in biopulping technology at Madison, WI -- Attempts to correlate biopulping benefits with changes in the chemical structure of wood components and enzymes produced during the wood biotreatment with Ceriporiopsis subvermispora -- Fungi as potential assisting agents in softwood pulping -- N-Hydroxy mediated laccase biocatalysis: recent progress on its mechanism and future prospect of its application -- Metal-activated laccase promoters -- Protease mediated processing of a Cu-induced laccase in Pleurotus ostreatus: a natural approach to improve protein stability -- Reactivity of high and low molar mass lignin in the laccase catalysed oxidation -- The effect of oxidation with single electron oxidants compared to laccase treatment of TMP wood fibres -- Studies on inactivation and stabilization of manganese peroxidase from Trametes versicolor -- Delving into the fundamental LMS delignification of high-kappa kraft pulps -- Elucidating of effects of laccase on the physical properties of high-kappa kraft pulps -- New developments in enzyme-assisted delignification and bleaching -- In vivo and in vitro biobleaching of unbleached hardwood kraft pulp by a marine fungus, Phlebia sp. MG-60 -- Potential of laccases in softwood-hardwood high-yield pulping and bleaching -- Pilot plant bleaching trials with laccase and mediator -- Flax pulp bleaching and residual lignin modification by laccase-mediator systems -- Biomimetic pulp bleaching with copper complexes and hydroperoxides -- Enzymatic degradation of oxalic acid for prevention of scaling -- Expression of thermophilic xylanases in fungal hosts -- Evaluation of bleach-enhancing effect of xylanases on bagasse pulp -- Boosting of LMS bleaching with hemicellulases -- Mill usage and mechanistic studies of xylanase to enhance bleaching -- Enzymatic control of dissolved and colloidal substances during mechanical pulping -- Enhancement of TMP reject refining by enzymatic modification of pulp carbohydrates -- A mill study -- Improved papermaking by cellulase treatment before refining -- The effects of recombinant Cellulomonas fimi [beta]-1,4-glycanases on softwood Kraft pulp fibre and paper properties -- Enzyme treatments for improved retention in newsprint stocks -- Potential of enzymatic deinking.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Elsevier
Keywords: Wood-pulp -- Biotechnology -- Congresses; Biotechnology; Wood; Paper; TECHNOLOGY & ENGINEERING -- Technical & Manufacturing Industries & Trades; Wood-pulp -- Biotechnology; Electronic books